ANATOMI DAN KUALITAS SERAT SEMBILAN JENIS KAYU KURANG DIKENAL ASAL KALIMANTAN TIMUR - Y I Mandang; Usep Sudardij (Jurnal Penelitian Hasil Hutan, 2001)
One way to overcome the shortages of raw material for wood based industries in Indonesia nowadays is to utilize the lesser known wood species. Therefore, the basic properties of these lesser known wood species should be studied. Wood anatomy of nine lesser known wood species from East Kalimantan have been observed and described for identification purposes and for evaluation of their properties and then appropriate uses.For identification purpose several main features have been noted : 1) Perforation plat scalariform in Mastixia trichotoma and Drypetes sp.; 2) Closely spaced parenchyma bands and radial intercellular canal in Ficus variegata; 3) Parenchyma reticulate in Drypetes sp, Diospyro macrophylla and Koilodepas sp.; 4) Fiber septate in Glochidion philippicum; 5) Rays almos exlusively homocelullar with gum-like deposite in vessels o/Lansium sp.Seven out of nine wood species examined containfibers of medium quality for pulp and paper among others : Blumeodendron kurzii, Ficus variegata and Mastixia trichtoma. The other two species contain fibers with poor quality. Two species, Drypetes sp. and Koilodepas sp. have light colour and decorative appearance and with considerable strength to be used as raw material for fancy furniture and decorative panel. Ficus variegata has anatomical structure which allow it too easily be peeled in to fine decorative veneer for plywood.Key words : Lesser known wood species, wood anatomy, identification, fiber quality.